Kesenian Disabilitas di Kota Makassar - Slamet - Thohari (Sociology Department, Brawijaya University, 2020)
The government and the people of Makassar have not paid attention to disability arts. The government does not provide serious and professional arts training to persons with disabilities. Disability art is only considered as an activity to fill leisure time and only displayed to intersperse events held by the government. Disability art is not seen as a serious work by the public. People only see from the side of their disability they assume that a person with a disability who has a work is an extraordinary thing and makes it inspiration inspiration. Disability and arts organizations collaborate and continue to struggle to bring up new works so that art is not only for non-disabled people. This new art was raised so that disability art was taken seriously and became a profession.